Eco-Friendly OTOP Production for Sustainable Society: A case study of Thailand - Nildam, Suwat; Rawang, Wee; Kliengchuay, Wissanupong; Tantrakarnapa, Kraichat (Journal of Ecohumanism, 2024)
The government of Thailand launched the OTOP program as a grassroots economic development strategy in 2001, and it has been functioned nationwide. However, some instances of environmental pollution occurred over a decade due to human activities. This research aimed to develop an environmental education strategy that enhance eco-friendly production and respond to the sustainability concept. The participatory action and survey research were applied. The policy makers and key informants were the target groups of this study namely; 10 policy executives, 25 entrepreneurs, and 20 OTOP representatives, meanwhile, structured-questionnaire was applied among 411 consumers. The results showed that the awareness level for pollution problems and participation in environmental conservation activities among the stakeholders were high. Majority of participants have high level of knowledge, attitude, skills and practices on eco-friendly production. The strategy based on sufficiency economy philosophy was developed, whereas four strategies with specific goals, measures, and 19 associated projects included. Expert evaluation and quality assessment were carried out, and showed that the strategy is highly rated in terms of satisfaction and confidence. As recommendations, the government agencies and stakeholders should promote targeted education and awareness programs about integrated eco-friendly OTOP production. Comprehensive learning centers, integrated budgets, initiatives for green marketing and communication strategies should be encouraged. Further in-depth research should be conducted for creative OTOP and green products to get better understanding about the overall market dynamics and respond to the sustainable concept of society.